Complex rift geometries resulting from inheritance of pre-existing structures: Insights and regional implications from the Barmer Basin rift. (February 2015) - Bladon, Andrew J.; Clarke, Stuart M.; Burley, Stuart D.
Abstract: Structural studies of the Barmer Basin in Rajasthan, northwest India, demonstrate the important effect that pre-existing faults can have on the geometries of evolving fault systems at both the outcrop and basin-scale. Outcrop exposures on opposing rift margins reveal two distinct, non-coaxial extensional events. On the eastern rift margin northwest–southeast extension was accommodated on southwest- and west-striking faults that form a complex, zig-zag fault network. On the western rift margin northeast–southwest extension was accommodated on northwest-striking faults that form classical extensional geometries. Combining these outcrop studies with subsurface interpretations demonstrates that northwest–southeast extension preceded northeast–southwest extension. Structures active during the early, previously unrecognised extensional event were variably incorporated into the evolving fault systems during the second. In the study area, an inherited rift-oblique fault transferred extension from the rift margin to a mid-rift fault, rather than linking rift margin fault systems directly. The resultant rift margin accommodation structure has important implications for early sediment routing and depocentre evolution, as well as wider reaching implications for the evolution of the rift basin and West Indian Rift System. The discovery of early rifting in the Barmer Basin supports that extension along the West Indian Rift System was long-lived, multi-event, and likely resulted from far-field plate reorganisations. Highlights: First description of the structure of the Barmer Basin, with fault maps. Outcrop and subsurface studies show evidence for two non-coaxial extension events. Northwest–southeast extension preceded northeast–southwest extension. Structural inheritance generated irregular accommodation structures. We suggest NW Indian rifting was long-lived & resulted from plate boundary forces.